Role of care in knowledge creation : the case of management consultancy. - Ott, Alexander. (2008)
This dissertation presents a contribution to the development of a knowledge based view of the firm. It specifically deals with the question how to enable new knowledge creation in order to gain a sustainable competitive advantage. Organisational knowledge creation as modeled by Nonaka et.al. is a fragile social process. This process has to be enabled, in order to result in innovative products and services. The dissertation addresses the question of the appropriate team climate for new knowledge creation in a consulting company.